Scaling behavior of dynamic hysteresis in soft lead zirconate titanate bulk ceramics - Rattikorn Yimnirun (2018)
The scaling behavior of the dynamic hysteresis of ferroelectric bulk system was investigated. The scaling relation of hysteresis area 〈A〉 against frequency f and field amplitude E0 for the saturated loops of the soft lead zirconate titanate bulk ceramic takes the form of 〈A〉 f-14 E0, which differs significantly from that of the theoretical prediction and that of the thin film. This indicates that the scaling relation is dimension dependent and that depolarizing effects in the interior must be taken into account to model bulk materials. Additionally, the scaling relation for the minor loops takes the form of 〈A〉 f-13 E03, which is identical to that of the thin film as both cases contain similar 180° domain-reversal mechanism. © 2006 American Institute of Physics.